The cost-effectiveness of prophylaxis strategies for individuals with advanced HIV starting treatment in Africa - Walker, SM; Cox, E; Revill, P; Musiime, V; Bwakura-Dangarembizi, M; Mallewa, J; Cheruiyot, P; Maitland, K; Ford, N; Gibb, DM; Walker, AS; REALITY Trial Team (Wiley, 2020)
Introduction: Many HIV-positive individuals in Africa have advanced disease when initiating antiretroviral therapy (ART) so have high risks of opportunistic infections and death. The REALITY trial found that an enhanced-prophylaxis package including fluconazole reduced mortality by 27% in individuals starting ART with CD4 <100 cells/mm3. We investigated the cost-effectiveness of this enhanced-prophylaxis package versus other strategies, including using cryptococcal antigen (CrAg) testing, in individuals with CD4 <200 cells/mm3 or <100 cells/mm3 at ART initiation and all individuals regardless of CD4 count.